Information and Digital Competence as a Key Demand of Modern Ukrainian Education - Anastasiia Chernenko (Educational Challenges)
Nowadays, digitalization in education is a digital transformation that is not a trend but a requirement of the times. Thus, the main task of teaching is the introduction of digital technologies, which provide education improvement, accessibility and efficiency, training the young generation for life in the digital society. Digital technologies are changed, in turn, it requires students and teachers to improve their knowledge, skills and to focus on the development. Information and digital competence in the education process helps teachers to teach the content effectively using the latest means that contribute to the achievement of the best results. With the development of key competencies, as an information and digital one, there is an urgent need to form it in the process of learning.